Accrual accounting transition in Federal government of Malaysia: Current status and challenges / Khairunnisa Yahya - Khairunnisa , Yahya (2024)
The International Public Sector Accounting Standards (IPSAS) were purportedly grounded the accounting reforms, providing governments across the globe with the opportunity to improve fiscal transparency, accountability and performance. Taking Federal Government of Malaysia (FGoM) as the setting, the research seeks to understand the current progress in the adoption of Malaysia Public Sector Accounting Standards (MPSAS) (accrual-based IPSAS), identify major challenges that occur during implementation phases as well as assess the effectiveness of accrual financial reporting from the implemented reform. Drawing on institutional change model from a theoretical standpoint, the research acknowledges that ongoing reforms are influenced by the political and socioeconomic environment, acting as barriers and causing delays. Research findings also highlights the importance of well-structured governance and comprehensive reform strategy. The data reveals challenges during the transition phase, including the complexity of developing a financial system for a large and distinctive government, as well as difficulties in managing organizational cultural change, capacity building, and expertise. Furthermore, the findings indicate that accrual-based reporting is perceived as a powerful tool for enhancing fiscal accountability and transperancy, while also emphasizing the importance of cautious disclosure to prevent misinterpretation. This research also underscores the need for a holistic approach during the design and implementation of accounting reforms. It prompts policymakers and practitioners to tailor reform strategies to the specific context of their respective jurisdictions.